Chapter 9: Major Drug Classes II (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
AuthorMr. Prakash Nathaniel Kumar Sarella, Associate Professor, Department of Pharmaceutics, Aditya College of Pharmacy, Aditya University, Surampalem, Andhra Pradesh, IndiaAbstractMajor drug classes involving infectious diseases, neurological conditions, pain, and cancer represent critical therapies for acute and chronic conditions requiring specialized knowledge. Antimicrobial agents include antibacterials classified by mechanism (cell wall inhibitors, protein synthesis inhibitors, DNA/RNA disruptors) and spectrum; antivirals targeting specific viral replication steps for HIV, hepatitis, herpes, and respiratory infections; antifungals addressing superficial and systemic mycoses; and antiparasitics, with selection guided by microbial identification, susceptibility, pharmacokinetic considerations, and antimicrobial stewardship principles preventing resistance development. Central nervous system drugs include antidepressants spanning multiple mechanisms (SSRIs, SNRIs, atypical agents); antipsychotics divided into conventional and atypical classes with varying receptor profiles; mood stabilizers for bipolar disorder; anxiolytics with particular attention to dependence potential; and anticonvulsants categorized by seizure type indication and molecular targets, each requiring specific monitoring for efficacy and unique adverse effect profiles. Pain management medications range from non-opioid analgesics (acetaminophen, NSAIDs) to opioids with varying potency, duration, and formulations; adjuvant agents including anticonvulsants and antidepressants for neuropathic pain; and topical analgesics, with therapy selection balancing efficacy against adverse effects, tolerance, and abuse potential through multimodal approaches. Oncology drugs include traditional cytotoxic agents classified by mechanism (alkylating agents, antimetabolites, microtubule inhibitors); targeted therapies addressing specific molecular pathways; immunotherapies enhancing anti-tumor immune responses; hormone therapies for receptor-positive cancers; and supportive care medications managing treatment side effects, each requiring specialized handling, complex administration protocols, and comprehensive monitoring for potentially severe adverse reactions.Keywords: Pathogen-Specific Therapy; Neurotransmitter; Receptor Modulation; Multimodal Analgesia; Targeted Treatment; Drug ResistanceVIEW PDF